ESTIMATION OF EFFICACY OF THE THREATMENT PREVENTIVE COMPLEX IN PATIENTS WITH GENERALIZED PERIODONTITIS, WORKING IN CONDITIONS OF GREENHOUSES UNDER THE INFLUENCE OF PESTICIDES ON SEPARATE PARAMETERS OF THE ORAL LIQUID - T. D. Zabolotnyj; N. N. Bandrivska; V. T. Dyryk (Ukrainian Medical Stomatological Academy, 2017)
Abstract. The periodontal diseases are one of the most common and difficult in the treatment and clinical conduction among the dental diseases. A significant prevalence of periodontal diseases in workers, contact in the process of activity with the unfavorable factors of production environment is relevant and unsolved problem of dentistry. In recent years, the conditions of labour on majority agroindustrial productions tested considerable changes, and their unfavorable characters are established: the amount of production with the low level of sanitary and technological disciplines increased, the system of medical providing of workers, that resulted to rolling up of preventive activity on enterprises and, as a consequence, increase of professional morbidity. The purpose of this research was to estimate the efficacy of use therapeutic preventive complex in patients with generalized periodontitis, working in greenhouses under the influence of pesticides on separate parameters of the oral liquid. The material and research methods. A complex treatment of inflammatory diseases of periodontal tissues was conducted for 120 workers of greenhouses with generalized periodontitis (71 patient of the main group and 49 persons of the control group). Patients with inflammatory diseases of periodontal tissues, which constituted the control group, were treated according to the "Protocols of the Ministry of Healthcare of Ukraine" by specialty "Therapeutic dentistry". Efficacy of the conducted treatment was estimated by the changes of content of medium molecular peptides (MMP) using methodology of А. А. Тоgaibaev and concentrations of lysozyme and sIgA in the oral liquid. The obtained results were worked out statistically. Results of the research and their discussion. For estimation of efficacy of the treatment, using our proposed treatment and preventive complex in patients with inflammatory diseases of periodontal tissues working in agroindustrial production on open and closed soils under the influence of pesticides, the dynamics of changes of the values of medium molecular peptides in the oral liquid in remote treatment terms were analyzed. In 6 months after the treatment in patients with CCG of the main group, the content of MMP in the oral liquid decreased on 31.82 % (0.255±0.03 conv. units of opt. density), p<0.05, while in patients of the control group the value of analyzed indicator increased on 2.60 %, p>0.05. As a result of studies it has been established that in patients with inflammatory diseases of periodontal tissues of the main group in 6 months after the treatment the content of lysozyme and sIgA in the oral liquid increased to 424.20±7.30 mcg/ml and to 0.249±0.016 g/l, respectively, p<0.01. Patients of the control group had a similar tendency: investigated increase of the content of lysozyme in the oral liquid to 393.50±7.25 mg/ml, p<0.05 and sIgA - to 0.225±0.017 g/l, p>0.05. In 12 months after the treatment in patients of the main group, a positive dynamic of increase of immunological parameters was saved. Thus, the content of lysozyme in the oral liquid increased on 22.12 %, the concentration of sIgA increased on 61.11 % compared to the data before treatment, p<0.01. In patients of the control group with inflammatory diseases of periodontal tissues in 12 months after the treatment the value of analyzed immunological parameters decreased and equaled to the data before treatment. Conclusions. The results of conducted studies have shown high efficacy of the worked out complex of the treatment preventive measures for workers of greenhouses with inflammatory diseases of periodontal tissues, working in the conditions of open and closed soils under the influence of pesticides. The efficacy of treatment preventive complex is significantly confirmed by the decrease of level of medium molecular peptides and increased levels of lysozyme and secretory immunoglobulin in the oral liquid.